Religiousness, Love of Money, and Ethical Attitudes of Malaysian Evangelical Christians in Business - Wong, Hong Meng (Journal of business ethics, 2008)
Recent research suggests there may be a link between religiousness and business ethics. This study seeks to add to the understanding of the relationship through a questionnaire survey on Malaysian Christians in business. The questionnaire taps into three different constructs. The religiousness construct is reflected in the level of participation in various common religious activities. The love of money construct is captured through the Love of Money Scale as used in Luna-Arocas and Tang [Journal of Business Ethics 50 (2004) 329]. Response to 25 business vignettes taken from Conroy and Emerson [Journal of Business Ethics 50 (2004) 383] would surface ethical attitudes. A convenience sample of 300 was drawn from three large churches in the Kuala Lumpur area each with a congregation exceeding 1000 together with some representation from the smaller churches. The study finds some differences in the ethical attitudes of Malaysian Christians in business with different levels of religiousness. The study also finds that those longer in the faith are less accepting of unethical behavior. As such it can be concluded that there are ethical attitude differences between Christians in business with different levels of religiousness. This lends support to the claim of a positive relationship between religion and business ethics. The more significant finding is that even within a somewhat homogenous religious group there are different love of money profiles resulting in significant differences in ethical attitudes. This suggests that moderating money attitudes can contribute towards stronger ethical attitudes.